"Not my boxes anyway": textual intersections of gendered, sexual and racial identities in post-aprtheid South Africa - Pinheiro, Gabriela Sofia (My University, 2018)
The perpetual construction of black lesbian women’s identities with discourses of risk and pathology is problematic, reinforcing stereotypes that blackwash homophobia. Blackwashing discourse invisibilises the complexity, fluidity and plurality implicated in the construction and performance of identities. Further, risk paradigms conceal the agency and power that many black lesbian women demonstrate in their negotiation of post-apartheid spaces. The current study aimed to explore possible ways in which black lesbian women construct and perform their identities in post-apartheid South Africa. Activism performed by, and for, black lesbian women was focalised in the research, diverging from discourses of blackwashing homophobia. Underpinned by feminist, intersectionality theory, a pluralist methodological approach was implemented, combining performativity theories with Feminist Critical Discourse Analysis. The data analysed was naturally-occurring, comprising online materials produced by black lesbian female activists. The findings of the study highlighted that black lesbian women in post-apartheid South Africa construct and perform multi-faceted identities. Moreover, discourses of violence featured minimally in participants’ constructions, compared to that which has been foregrounded previously. Instead, discourses of power, agency, activism and resilience emerged – attesting the intricate possibilities that exist at the intersections of gendered, sexual and racial identities in contemporary South Africa.
A Research Report submitted in partial fulfillment of the requirements for the degree of Master of Arts in Social and Psychological Research (by Coursework and Research Report) Faculty of the Humanities University of the Witwatersrand 2018
Keywords: Lesbians--South Africa; Women, Black--South Africa; Identity (Psychology)